Light intensity dependence of organic solar cell operation and dominance switching between Shockley–Read–Hall and bimolecular recombination losses - Ryu, Shinyoung; Ha, Na Young; Ahn, Y. H.; Park, Ji Yong; Lee, Soonil (Scientific Reports, 2021)
We investigated the variation of current density–voltage (J–V) characteristics of an organic solar cell (OSC) in the dark and at 9 different light intensities ranging from 0.01 to 1 sun of the AM1.5G spectrum. All three conventional parameters, short-circuit currents (Jsc), open-circuit voltage (Voc), and Fill factor (FF), representing OSC performance evolved systematically in response to light intensity increase. Unlike Jsc that showed quasi-linear monotonic increase, Voc and FF showed distinctive non-monotonic variations. To elucidate the origin of such variations, we performed extensive simulation studies including Shockley–Read–Hall (SRH) recombination losses. Simulation results were sensitive to defect densities, and simultaneous agreement to 10 measured J–V curves was possible only with the defect density of 5×1012cm-3. Based on analyses of simulation results, we were able to separate current losses into SRH- and bimolecular-recombination components and, moreover, identify that the competition between SRH- and bimolecular-loss currents were responsible for the aforementioned variations in Jsc, Voc, and FF. In particular, we verified that apparent demarcation in Voc, and FF variations, which seemed to appear at different light intensities, originated from the same mechanism of dominance switching between recombination losses.